Correlation between virulence factor and biofilm formation in Proteus spp. - S.Qaddoorri, Sarah; A. Laftaah, Bahaa; N. AbdALgani, Murtada; K.ALSegar, Rabab; S.Abd-ALkadir, Sawsan; J.Ali, Yousra; H.A- Neddawi, Tahreer (Iraqi Journal of Science, 2023)
Urinary Tract Infection is an infection that caused by the members of the genusProteus that depends mainly on the availability of virulence factors ;Variousvirulence factors including biofilm, swarming migration , polysaccharide,heamolysin,protease, DNase, urease production weredetermined for 45Proteusisolates that obtained from clinical specimens of Urinry Tract Infection patient .The distribution of virulence factors was showed variation among the testedisolatesand strain specific in most cases. All Proteus isolates showed 45 (100%)biofilm ,polysaccharide andSwarming capabilities with different extents. Highureaseproduction was demonstrated in most isolates 40 (88.8%);In addition, theywere abling to produce protease,DNase and heamolysin, in 30(66.6%) , 28 (62.2%)and26(57.7%) respectively.The result of susceptibility test for Proteus spp. against seven antibioticscommonly used to treat UTI infection caused by Proteus spp. ; P.mirabilis were90% sensitive for Meropenem , 80% to Ciprofloxacin , 60% for both Cephalothin ,Nitrofurantion , 50% , 40% and 30% for Amikicin, gentamicin and ceftriaxonerespectively ,butP.vulgaris isolates were sensitive to 80% for Meropenem ,70%Ciprofloxacin and Nitrofurantion and sensitive to 60%,50% ,40 % and 30 % forCephalothin, gentamicinAmikacinand ceftriaxone respectively.(This studyaimed todetect and evaluate the presence of some virulence factors in Proteus speciesisolates causing Urinry Tract Infection